Mycobacterium abscessus Strain Morphotype Determines Phage Susceptibility, the Repertoire of Therapeutically Useful Phages, and Phage Resistance - Dedrick, Rebekah M. (mBio, 2021)
Mycobacterium abscessus is an opportunistic pathogen whose treatment is confounded by widespread multidrug resistance. The therapeutic use of bacteriophages against Mycobacterium abscessus infections offers a potential alternative approach, although the spectrum of phage susceptibilities among M. abscessus isolates is not known. We determined the phage infection profiles of 82 M. abscessus recent clinical isolates and find that colony morphotype—rough or smooth—is a key indicator of phage susceptibility. None of the smooth strains are efficiently killed by any phages, whereas 80% of rough strains are infected and efficiently killed by at least one phage. The repertoire of phages available for potential therapy of rough morphotype infections includes those with relatively broad host ranges, host range mutants of Mycobacterium smegmatis phages, and lytically propagated viruses derived from integrated prophages. The rough colony morphotype results from indels in the glycopeptidolipid synthesis genes mps1 and mps2, negating reversion to smooth as a common route to phage resistance. Resistance is thus rare, and although mutations in polyketide synthesis, uvrD2, and rpoZ can confer resistance, these likely also impair survival in vivo. The expanded therapeutic repertoire and the resistance profiles show that small cocktails or single phages could be suitable for controlling infections with rough strains.